Katekese Inkulturasi Tentang Makna Budaya "Arat Sabulungan" Dalam Masyarakat Suku Mentawai - Maria Sonniati Satoko; Intansakti Pius X (Jurnal Pelayanan Pastoral, 2023)
The relationship between church and culture has been a long discussion. The culture that exists in the world should be a valuable part of the life of the church. The world and society, with all their forms, characters, and social conditions, display diversity. In the culture of society, of course, there are many good and valuable values. The "Arat Sabulungan" culture in Mentawai society is one of the many cultures that have noble values. Arat Sabulungan is a custom that involves belief in the existence of spirits and spirits who inhabit all of nature, including plants, animals, soil, and man-made objects. Basically, Arat Sabulungun is the knowledge, values, rules, and norms used by people to understand and interpret their environment, including interactions between humans, animals, plants, land, water, air, and man-made objects. The values contained in the "Arat Sabulungan" culture can be seen and interpreted both from a social, moral, and spiritual perspective. These good values are then adopted into the life of the church. By seeing the importance of paying attention to the relationship between the Church and culture, the focus of this writing study is the Inculturation Catechism on the meaning of the Arat Sabulungan Culture in the Mentawai tribal community. The method used is literature and interviews, so the values contained in the Arat Sabulungan culture, such as honesty, cooperation, solidarity, and mutual respect, are found to be relevant in increasing understanding of the teachings of the Catholic Church by the Mentawai people.